2010
DOI: 10.1353/jod.2010.0012
|View full text |Cite
|
Sign up to set email alerts
|

The Meanings of Democracy: The Shadow of Confucianism

Abstract: Scholars have been puzzled by the high level of support for democracy, as well as the high level of support for the authoritarian regime, in China, as revealed in numerous surveys. In this paper, Shi and Lu argue that people in different societies may understand democracy in distinct ways. Confucian culture defines democracy in terms of Minben , which is different from the procedural understanding of democracy following the liberal tradition. These two definitions generate different expectations for the govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 9 publications
2
21
0
1
Order By: Relevance
“…More than different regime types, culture may shape understandings of democracy. Research on China and Asia has suggested that Confucian tradition leads to an alternative definition of democracy where governing legitimacy comes from positive social outcomes, not electoral procedures (Shi and Lu 2010). We adopt two strategies from the literature to address the challenges of measuring democratic attitudes across culture and context.…”
Section: A T Amentioning
confidence: 99%
“…More than different regime types, culture may shape understandings of democracy. Research on China and Asia has suggested that Confucian tradition leads to an alternative definition of democracy where governing legitimacy comes from positive social outcomes, not electoral procedures (Shi and Lu 2010). We adopt two strategies from the literature to address the challenges of measuring democratic attitudes across culture and context.…”
Section: A T Amentioning
confidence: 99%
“…In a free democracy, such participation is the fundamental right guaranteed by the social contract between citizens and their government. In the doctrine of the "people as the roots," however, the political participation of civilians is limited to expressing their concerns with the authorities (Shi and Lu 2010). With this view, it is not easy to concede that Confucianism is democratic or antidemocratic.…”
Section: "Democracy" In Vietnamese Societymentioning
confidence: 99%
“…In other words, the societal agreements on the form of democracy might vary substantially across different societies, and such variations are largely neglected in the attempts to operationalize a "common" definition of democracy. For example, Tianjian and Jie [8] argued that majorities in China are driven by Confucian concept of democracy, claiming strong support for collectivism and, at the same time, a high level of satisfaction with the country"s authoritarian regime, which is in sharp contrast to many western countries. In Confucian theory, the most important premise of a democratic society is the assurance of societal harmonythe democratic processes should only be taken place with the presence of great order.…”
Section: Introductionmentioning
confidence: 99%